2007
DOI: 10.1051/forest:2006086
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive success of a Quercus petraea × Q. robur F1-hybrid in back-crossing situations

Abstract: -A 56 year old Quercus petraea × Q. robur F1-hybrid was back-crossed to both parental species. Pollen mixes were applied and paternity assigned to offspring based on microsatellite markers. The studied Q. petraea × Q. robur hybrid proved highly fertile and back-crossed well with both Q. robur and Q. petraea with slight but not significant preference for Q. robur. The results do not support the hypothesis about highly unidirectional gene flow between Q. robur and Q. petraea towards Q. robur as the observed back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…On the other hand, incompatibilities between F 1 hybrids and one or both parental species appeared to be reduced potentially facilitating gene fl ow between sympatric species with partial incompatibilities. For example, a rare Q. petraea x Q. robur F 1 hybrid could be backcrossed effi ciently with both parents possibly allowing nuclear gene fl ow from Q. robur to Q. petraea (Olrik & Kjaer 2007). Likewise, seeds collected from a hybrid between Q. lobata and Q. douglasii were fathered by both Q. lobata (37%) and Q. douglasii (63%), while only seven out of 394 Q. lobata acorns had mixed ancestry (Abraham et al 2011).…”
Section: Experimental Interspecific Crossesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, incompatibilities between F 1 hybrids and one or both parental species appeared to be reduced potentially facilitating gene fl ow between sympatric species with partial incompatibilities. For example, a rare Q. petraea x Q. robur F 1 hybrid could be backcrossed effi ciently with both parents possibly allowing nuclear gene fl ow from Q. robur to Q. petraea (Olrik & Kjaer 2007). Likewise, seeds collected from a hybrid between Q. lobata and Q. douglasii were fathered by both Q. lobata (37%) and Q. douglasii (63%), while only seven out of 394 Q. lobata acorns had mixed ancestry (Abraham et al 2011).…”
Section: Experimental Interspecific Crossesmentioning
confidence: 99%
“…However, cross-compatibility between F 1 hybrids and pure species (Olrik & Kjaer 2007, Lepais & Gerber 2011 suggested that reduced incompatibilities in hybrids might be a route for interspecifi c gene fl ow. Accordingly, a gene fl ow analysis in the four European white oak species Q. robur, Q. petraea, Q. pubsecens and Q. pyrenaica suggested that rare F 1 hybrids are compatible and show a high fi delity to both parental species, thus enabling gene fl ow between species, but preventing the evolution of hybrids swarms (Lepais & Gerber 2011).…”
Section: Gene Flow Analyses In Mixed Oak Standsmentioning
confidence: 99%
“…Particularly, it has been documented that habitat conditions (Williams and Ehleringer 2000;Williams et al 2001;Himrane et al 2004;Lagache et al 2013), geographical localization of the hybrid zone (Tovar-Sánchez and Oyama 2004), establishment and survivorship of hybrid individuals (ValbuenaCarabana et al 2007), different rates of gene flow (Curtu et al 2007), relative abundance and identity of species (Lepais et al 2009), spatial structure of species (Salvini et al 2009), or proportion of conspecific pollen and the density of individuals available to mating (Lagache et al 2013) can influence the levels of hybridization and introgression in oaks. Also, recent studies have reported that the reproductive barriers that operate among oak species involved in hybridization events changes between species pair (Curtu et al 2007;Jensen et al 2009;Lepais et al 2009Lepais et al , 2013, depending on which species act as maternal or paternal parental (Boavida et al 2001;Olrik and Kjaer 2007;Lepais et al 2013) and in response to environmental variation (Lepais and Gerber 2011;Abadie et al 2012;Lepais et al 2013). In consequence, variation in the richness of the local oak community and in ecological and geographical factors among sites could promote differences in the occurrence, types of hybrids and their frequency.…”
Section: Introductionmentioning
confidence: 98%
“…Artificial crosses involving F1s and the parental species would help determine the direction of introgression and the nature of barriers to random mating. For instance, Olrik and Kjaer (2007) showed that Q. robur-Q. petraea unidirectional hybridization does not imply necessarily asymmetric backcrossing to the parental species, after performing controlled crosses with an F1 tree of known pedigree.…”
Section: Detection Of Hybrids In Oaksmentioning
confidence: 99%